5 - Education de base et participation communautaire en Afrique subsaharienne: Réflexions sur l’orientation de la recherche : by Sibry Tapsoba - Sibry Tapsoba (Africa Development, 1994)
During the last three decades, governments in Sub-Saharan Africa have heavily invested in their formal education systems in terms of financial contribution, human resource allocation and the building of infrastructures. However, they were all disappointed with the results obtained Educational systems are now going through severe crises resulting in graduate unemployment, shortage of qualified technical skill, idleness of millions of school leavers, irrelevance of education in illation to the environment and erratic changes. The author's contention is that this failure is largely due to the fact that the communities have been marginalised in mapping out education policies, strategies and curricula An active involvement of the communities, properly consulted and conducted will, according to the author improve the education system significantly.